PENGARUH GAYA MENGAJAR TEKNOLOGIS GURU PENDIDIKAN AGAMA KRISTEN TERHADAP GAYA BELAJAR VISUAL SISWA KELAS VIII SMP N 1 PAHAE JULU K KABUPATEN TAPANULI UTARA TAHUN PEMBELAJARAN 2018/2019” - martha simorangkir (IAKN Tarutung, 2019)
vAbstract, The research aims to know of percentage the teknological teaching style of teachers christianeducation towards students visual learning styles in class VIII SMP Negeri 1 Pahae Julu Tapanuli Utararegency in 2018/2019 academic years. The hypothesis of this research was: there is a positive and significantinfluence teknological teaching style of teachers christian education towards students visual learning styles inclass VIII SMP Negeri 1 Pahae Julu Tapanuli Utara in 2018/2019 academic years.Research instrument in the form of a closed questionnaire prepared by the research. analyzing datawas indicated that the teknological teaching style of teachers christian education towards students visuallearning styles in class VIII SMP Negeri 1 Pahae Julu Tapanuli Utara by 16,40 % with the calculation bycomparing tcount ttable namely 2,426 2,042. Tes the regression equation between X and Y with.Hypothesis test indicated that the Fcount Ftable namely 5,870 1,62 then H0 rejected and Haaccepted. the conclusion drawn from this study was there is a positive and significant influence teknologicalteaching style of teachers christian education towards students visual learning styles in class VIII SMP Negeri 1Pahae Julu Tapanuli Utara regency in 2018/2019 academic years.Keywords : teknological teaching style of teachers christian education, students visual learning styles.